2020
DOI: 10.1525/cse.2020.1229632
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships Generate Co-Benefits in Agricultural Stream Restoration (Canterbury, New Zealand)

Abstract: In Aotearoa New Zealand, agricultural land-use intensification and decline in freshwater ecosystem integrity pose complex challenges for science and society. Despite riparian management programmes across the country, there is frustration over a lack in widespread uptake, upfront financial costs, possible loss in income, obstructive legislation and delays in ecological recovery. Thus, social, economic and institutional barriers exist when implementing and assessing agricultural freshwater restoration. Partnersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Implementing some or all of these practices calls for a coordinated approach to implementing multiple solutions across scales (Goeller et al, 2020), which can be achieved through cross-sector partnerships to achieve co-benefits for all (Febria et al, 2020). Several models were recently tested to evaluate predicted changes in landscape biodiversity resulting from the incorporation of many of the above practices, which demonstrated that policies and practices aimed at habitat conversion-enlarging the extent of land under various forms of conservation management, restoring degraded land, and increasing the incorporation of landscape-level conservation planning-could reverse decades-long declines in biodiversity by around the mid-21st century (Leclère et al, 2020).…”
Section: Parsing Transformative Change: the Environmental Benefits Of...mentioning
confidence: 99%
“…Implementing some or all of these practices calls for a coordinated approach to implementing multiple solutions across scales (Goeller et al, 2020), which can be achieved through cross-sector partnerships to achieve co-benefits for all (Febria et al, 2020). Several models were recently tested to evaluate predicted changes in landscape biodiversity resulting from the incorporation of many of the above practices, which demonstrated that policies and practices aimed at habitat conversion-enlarging the extent of land under various forms of conservation management, restoring degraded land, and increasing the incorporation of landscape-level conservation planning-could reverse decades-long declines in biodiversity by around the mid-21st century (Leclère et al, 2020).…”
Section: Parsing Transformative Change: the Environmental Benefits Of...mentioning
confidence: 99%